A multinational report of technical factors on stereotactic body radiotherapy for oligometastases - Redmond, Kristin J.; Lohr, Frank (Future oncology, 2017)
Aim: Oligometastatic cancer is being increasingly managed with aggressive local therapy using stereotactic body radiation therapy (SBRT). However, few guidelines exist. We summarize the results of an international survey reviewing technical factors for extracranial SBRT for oligometastatic disease to guide safe management. Materials & methods: Seven high-volume centers contributed. Levels of agreement were categorized as strong (6-7 common responses), moderate (4-5), low (2-3) or no agreement. Results & conclusion: We present the results of a multi-national and multi-institutional survey of technical factors of SBRT for extracranial oligometastases. Key methods including target delineation, prescription doses, normal tissue constraints, imaging and set-up for safe implementation and practice of SBRT for oligometastasis have been identified. This manuscript will serve as a foundation for future clinical evaluations.
Gesehen am 17.10.2018